"At This Defining Moment" : Barack Obama's Presidential Candidacy and the New Politics of Race - Logan, Enid (Book collections on Project MUSE., 2011)
Introduction: the landscape of race in the 21st century -- Post-race American triumphalism and the entrenchment of colorblind racial ideology -- Rooted in the Black community but not limited to it: the perils and promises of the new politics of race -- Contesting gender and race in the 2008 democratic primary -- The trope of race in Obama's America -- Asian and Latino voters in the 2008 election: the politics of color in the racial middle -- In defense of the white nation: the modern conservative movement and the discourse of exclusionary nationalism -- Racial politics under the first Black president.